Hypoxic training and perfomance - Roels, B.; Millet, G. P. (First international symposium sciences and practices in swimming, 2006)
A frequently asked question by athletes, coaches and scientists concerns the enhancement in sea-level performance by altitude training. To date, in spite of many scientific studies, no equivocal answer has been given. Thus, whether or not sea-level performance is enhanced by altitude training and which hypoxic method is the most efficient one remain controversial questions. Currently, several strategies are used. The traditional "living high-training high" method consists of a constant sojourn at altitude, i.e. living and training at altitude. Intermittent Hypoxic Exposure (IHE) refers to the discontinuous use of normobaric or hypobaric hypoxia, in an attempt to replicate some of the physiological adaptations to altitude, i.e. improved O2 delivery and utilization; for example "living high-training low or "living low-training high". Finally, the intermittent hypoxic interval training (IHIT) typically employs sustained exercise bouts alternated with periods of reduced intensity or complete rest. All these strategies have the ultimate goal to improve sea-level athletic performance. While research into intermittent hypoxia has accelerated in the recent years, many fundamental and applied questions still remain to be answered.